2021
DOI: 10.1111/trf.16566
|View full text |Cite
|
Sign up to set email alerts
|

Washing transplants with Sepax 2 reduces the incidence of side effects associated with autologous transplantation and increases patients' comfort

Abstract: Background: High-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (ASCT) is routinely used in various hematologic malignancies. However, dimethylsulfoxide contained in cryopreserved grafts can cause adverse events (AEs). Study design and methods: Forty-three ASCTs were performed with Sepax 2 washed grafts between 7/2016 and 10/2019. The aim of this study was to determine whether washing out dimethyl sulfoxide (DMSO) from transplants using the Sepax 2 (S-100) device is safe and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To avoid HPC losses as well as to reduce the risk of contamination, several techniques and methodologies have been developed for DMSO removal, replacing the conventional method which is based on manual removal after centrifugation [23]. An automated washing system, such as demonstrated by the present study, provides time sensitive alternative, optimizes the washing process and reduces the risk of contamination due to the closed fluid path 7, 16, 17. In 2011, Scerpa et al, showed that the automated washing procedure for DMSO removal, using the Sepax™ S-100 system, guarantees a better result in terms of recovering TNC, CD34 + /CD45 + cells and total CFU without affecting cell functionality, when compared to the manual centrifugation procedure 24 . In this study, the automated Sepax2™ system has proven an effective method for routine removal of DMSO from MPB cryopreserved grafts after thawing, with the mean recovery of TNC, viable CD34 + /CD45 + cells, CFU-GM count as well as maintaining test sterility of cell products.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid HPC losses as well as to reduce the risk of contamination, several techniques and methodologies have been developed for DMSO removal, replacing the conventional method which is based on manual removal after centrifugation [23]. An automated washing system, such as demonstrated by the present study, provides time sensitive alternative, optimizes the washing process and reduces the risk of contamination due to the closed fluid path 7, 16, 17. In 2011, Scerpa et al, showed that the automated washing procedure for DMSO removal, using the Sepax™ S-100 system, guarantees a better result in terms of recovering TNC, CD34 + /CD45 + cells and total CFU without affecting cell functionality, when compared to the manual centrifugation procedure 24 . In this study, the automated Sepax2™ system has proven an effective method for routine removal of DMSO from MPB cryopreserved grafts after thawing, with the mean recovery of TNC, viable CD34 + /CD45 + cells, CFU-GM count as well as maintaining test sterility of cell products.…”
Section: Discussionmentioning
confidence: 99%
“…The apheresis‐collected product is cryopreserved until the time of infusion for almost all patients preparing for auto‐PBSCT and most patients waiting for allo‐PBSCT, whereas it is immediately infused without cryopreservation occasionally in allo‐PBSCT recipients 4,5 . For cryopreservation, an appropriate dose of cryoprotectant is added to the PBSC product based on its volume for prevention of cellular injuries, such as intra‐ and extracellular ice formation and cell dehydration, due to storage at temperatures below −80°C or with liquid/vapor nitrogen 6–9 . The most commonly used cryoprotectant for a PBSC product is dimethyl sulfoxide (DMSO), which is a hygroscopic polar compound that penetrates the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For cryopreservation, an appropriate dose of cryoprotectant is added to the PBSC product based on its volume for prevention of cellular injuries, such as intraand extracellular ice formation and cell dehydration, due to storage at temperatures below À80°C or with liquid/ vapor nitrogen. [6][7][8][9] The most commonly used cryoprotectant for a PBSC product is dimethyl sulfoxide (DMSO), which is a hygroscopic polar compound that penetrates the cell membrane.…”
Section: Introductionmentioning
confidence: 99%